Case report: Applied behavior analysis in a case of anomic aphasia in post-acute myocardial infarction with cardiac arrest and brain hypoxia: results of tact-training - Catania, Valentina; D’Angelo, Guido; Panerai, Simonetta; Lanuzza, Bartolo; Ferri, Raffaele (Frontiers in Psychology, 2024)
Purpose Applied Behavior Analysis (ABA) tact-training was provided to an adult with post-stroke anomic aphasia, with the main purposes to improve naming of pictures, with a possible generalization to another different setting, through telehealth sessions. Method The Multiple probe experimental design across behaviors was used. Two sets of stimuli were used (SET 1 and SET 2), including 60 laminated photos, belonging to three different categories for each set. Procedure included the baseline, the intervention phases (face-to-face and telehealth sessions), and the follow-up (1 month after the end of a tact training). Results For both, SET 1 and SET 2, the mastery criterion (80% correct stimulus tacts, for three consecutive times, simultaneously for all categories) was achieved. No increased percentage of correct picture tacts was found for untrained items. At follow-up, the patient provided 70 to 100% correct responses. For both SET 1 and SET 2, telehealth did not modify the correct response trends. Conclusion The results of our study seem to suggest that specific tact-training procedures might be successfully carried out in adult and elderly people with post-stroke aphasia. It also appears necessary to arrange protocols providing telehealth sessions, with benefits for both families and the health system.